If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.5(-4+6x)=0.3x+0.7(x+9)
We move all terms to the left:
0.5(-4+6x)-(0.3x+0.7(x+9))=0
We add all the numbers together, and all the variables
0.5(6x-4)-(0.3x+0.7(x+9))=0
We multiply parentheses
3x-(0.3x+0.7(x+9))-2=0
We calculate terms in parentheses: -(0.3x+0.7(x+9)), so:We get rid of parentheses
0.3x+0.7(x+9)
We multiply parentheses
0.3x+0.7x+6.3
We add all the numbers together, and all the variables
x+6.3
Back to the equation:
-(x+6.3)
3x-x-6.3-2=0
We add all the numbers together, and all the variables
2x-8.3=0
We move all terms containing x to the left, all other terms to the right
2x=8.3
x=8.3/2
x=4+0.3/2
| 3x+2-5x=8+2x | | 3+-k=9 | | -3(1+6)=14-y | | 59049=(3)(3)^n-1 | | 47=3x^2 | | 10(2x+6)=8(2x+12) | | 2x-16=2(1+4x) | | 10(2x+6)=8(4x+12) | | 10(2x+6)=8(2x+6) | | F(54)=2x+10 | | 10(2x+6)=8(4x+6) | | 14j-14j+j-j+2j=18 | | 3x(10+9x−x^2)=0 | | 2x-2+3x-7+x+3=23 | | 5(x-1)=28-6x | | 6x-4=2(4x-4) | | 0.7x0.6=0.2x-0.42 | | 9p+4p+5p-14p=4 | | 30x+27x^2−3x^3=0 | | 6x3=3x6= | | 10(2x+6)=8(x+10) | | 10(2x+6)=8(x+8) | | 2(6x-1)+(2x+5)=90 | | -8=7x+3x-8 | | 10(2x+6)=8(x+5) | | 10(2x+6)=8(x+4) | | 10=-14+6b | | 30x+27x2−3x3=0 | | 10(2x+6)=8(x+1) | | 6a2=150 | | 13-0.5(2x-6)×2x=17 | | 4y-2=42 |